Paradoxical roles of autophagy in different stages of tumorigenesis: protector for normal or cancer cells - Sun, Kai (BioMed Central, 2013)
Autophagy serves as a dynamic degradation and recycling system that provides biological materials and energy in response to stress. The role of autophagy in tumor development is complex. Various studies suggest that autophagy mainly contributes to tumor suppression during the early stage of tumorigenesis and tumor promotion during the late stage of tumorigenesis. During the tumorization of normal cells, autophagy protects genomic stability by retarding stem cells-involved damage/repair cycle, and inhibits the formation of chronic inflammatory microenvironment, thus protecting normal cell homeostasis and preventing tumor generation. On the other hand, autophagy also protects tumor cells survival during malignant progression by supporting cellular metabolic demands, decreasing metabolic damage and supporting anoikis resistance and dormancy. Taken together, autophagy appears to play a role as a protector for either normal or tumor cells during the early or late stage of tumorigenesis, respectively. The process of tumorigenesis perhaps needs to undergo twice autophagy-associated screening. The normal cells that have lower autophagy capacity are prone to tumorization, and the incipient tumor cells that have higher autophagy capacity possibly are easier to survival in the hash microenvironment and accumulate more mutations to promote malignant progression.